Erratum: Using Non-Probability Sampling Methods in Agricultural and Extension Education Research - JIAEE Editors (Journal of International Agricultural and Extension Education, 2024)
Correction: The DOI of the article "Lamm, A. J., & Lamm, K. W. (2019). Using Non-Probability Sampling Methods in Agricultural and Extension Education Research. Journal of International Agricultural and Extension Education, 26(1), 52-59” was incorrect as published. The correct DOI is: 10.5191/iaee.2019.26105